Boundary value problems on the half-line for a generalised Painlevé II equation - Amster, Pablo Gustavo (2009)
Two types of boundary value problem on the infinite half-line are investigated for a class of generalised Painlevé II equations. Existence results are obtained via the method of upper and lower solutions together with a diagonal argument.